2021
DOI: 10.1074/jbc.ra120.014726
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a peptide ligand for the adhesion GPCR ADGRG2 provides a potent tool to explore receptor biology

Abstract: The adhesion GPCR ADGRG2, also known as GPR64, is a critical regulator of male fertility that maintains ion/pH homeostasis and CFTR coupling. The molecular basis of ADGRG2 function is poorly understood, in part because no endogenous ligands for ADGRG2 have been reported, thus limiting the tools available to interrogate ADGRG2 activity. It has been shown that ADGRG2 can be activated by a peptide, termed p15, derived from its own N-terminal region known as the Stachel sequence. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Several studies analyzing the role of the amino acids composing the tethered agonist are in accordance with our identification of phenylalanine at position 3, as the most N-terminal residue playing a key role in aGPCR activation (GPR64/ADGRG2, Azimzadeh et al, 2019 andSun et al, 2020;GPR126, Liebscher et al, 2014;Lphn3/ADGRL3, Mathiasen et al, 2020). Similarly, amino acids at positions 6 and 7, albeit not strictly conserved as leucine and methionine residues in all aGPCR tethered ligands, Leucine 998 and Methionine 999 are key for GPR116 activation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Several studies analyzing the role of the amino acids composing the tethered agonist are in accordance with our identification of phenylalanine at position 3, as the most N-terminal residue playing a key role in aGPCR activation (GPR64/ADGRG2, Azimzadeh et al, 2019 andSun et al, 2020;GPR126, Liebscher et al, 2014;Lphn3/ADGRL3, Mathiasen et al, 2020). Similarly, amino acids at positions 6 and 7, albeit not strictly conserved as leucine and methionine residues in all aGPCR tethered ligands, Leucine 998 and Methionine 999 are key for GPR116 activation.…”
Section: Discussionsupporting
confidence: 71%
“…It will be interesting to identify the position of ECL2 in the peptide-activated state. As an extreme example, in GPR52, a class A receptor, it was recently shown that ECL2 can act as a tethered ligand and activates the receptor by interacting with the TM barrel (Lin et al, 2020). This is yet another potential mechanism of aGPCR activation and cannot be excluded for other members of the aGPCR family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While finalizing this manuscript, we noticed that a separate group reported that several residues, including the tryptophan and isoleucine of the ECL2, participate in the binding of Stachel peptide to ADGRG2 37 . Although this study corroborates some of our findings, differences exist between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the ECL2 of other aGPCRs play similar roles in receptor stability and activation by Stachel peptides warrants further studies. While finalizing this manuscript, we noticed that a separate group reported that several residues, including the tryptophan and isoleucine of the ECL2, participate in the binding of Stachel peptide to ADGRG2 37 . Although this study corroborates some of our findings, differences exist between the two studies.…”
Section: Stachel On the Cognate Agpcr Remains Largely Unknown Structmentioning
confidence: 99%